Pivot to Africa: Uncovering Indonesia’s Economic Diplomacy in Africa Region - Achmad Ismail; Darynaufal Mulyaman (Journal Social Politica, 2026)
The South African region with its large population is an attraction for Indonesia to be used as an alternative (non-traditional) market share. Indonesia's economic diplomacy was then directed to the African Region. This research aims to analyze the implementation of Indonesia's economic diplomacy in the African region, especially in Egypt and South Africa, in order to expand economic cooperation and increase Indonesia's influence at the global level. This study uses a qualitative method with a descriptive analysis approach. This research uses data collection techniques through secondary data (literature studies) obtained from journal articles, books, media and so on. This article uses the theory or concept of economic diplomacy. The results of the study show that Indonesia's proactive economic diplomacy efforts in the African region, especially Egypt and South Africa, have an impact on Indonesia's economy. Economic diplomacy in the African region is carried out not only bilaterally, but also multilaterally, for example the Indonesia-Africa Forum. Not only does it have an impact on the economy, it is also political, such as increasing Indonesia's bargaining power or influence in the African region and in the international world.